2017
DOI: 10.1016/j.jacc.2016.12.022
|View full text |Cite|
|
Sign up to set email alerts
|

Neutrophil Counts and Initial Presentation of 12 Cardiovascular Diseases

Abstract: BackgroundNeutrophil counts are a ubiquitous measure of inflammation, but previous studies on their association with cardiovascular disease (CVD) were limited by small numbers of patients or a narrow range of endpoints.ObjectivesThis study investigated associations of clinically recorded neutrophil counts with initial presentation for a range of CVDs.MethodsWe used linked primary care, hospitalization, disease registry, and mortality data in England. We included people 30 years or older with complete blood cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
86
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 114 publications
(93 citation statements)
references
References 30 publications
6
86
0
1
Order By: Relevance
“…Inflammation could be triggered by comorbidities such as diabetes or obesity or via endothelial dysfunction and atherosclerosis from an underlying heart disease; however, it remains to be investigated how inflammation and HF interact exactly. Similar results have recently been reported for other CVDs . Additionally, we found an association of creatinine and an inverse association of haemoglobin with incident HF.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Inflammation could be triggered by comorbidities such as diabetes or obesity or via endothelial dysfunction and atherosclerosis from an underlying heart disease; however, it remains to be investigated how inflammation and HF interact exactly. Similar results have recently been reported for other CVDs . Additionally, we found an association of creatinine and an inverse association of haemoglobin with incident HF.…”
Section: Discussionsupporting
confidence: 91%
“…We confirmed several associations of risk factors with HF, such as diabetes, BMI, and smoking. Our study supports and contributes to previous studies in CALIBER, which have shown associations of these risk factors with a range of CVDs. We observed similar patterns of association between men and women as well as attenuation of the associations of risk factors with HF at older age.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This relationship continued to approach significance even when percent body fat was included in the model, indicating the relationship is not solely due to obesity. Increased white cell counts have been shown to predict arterial stiffness in adults in a variety of conditions and increased neutrophil counts predict future cardiovascular disease in adults . The increased neutrophil counts are thought to be evidence of increased endothelial inflammatory damage.…”
Section: Discussionmentioning
confidence: 99%
“…EHR phenotypes have been developed in CALIBER for acute Ml,(15) atrial fibrillation,(25) and stable coronary disease(26). Cohort studies of their associations with blood pressure,(27) diabetes,(28) smoking,(29) socioeconomic deprivation,(30) rheumatoid arthritis,(31) alcohol consumption(32) and neutrophil counts(33) have supported their validity.…”
Section: Introductionmentioning
confidence: 99%